Teams Games Tournament (TGT) Sebagai Metode dalam Peningkatan Motivasi dan Prestasi Belajar Matematika Siswa - Maftuhin Maftuhin (Universitas Hamzanwadi, 2021)
While the objectives of this study are: (a) Increase the motivation to learn Mathematics of SMA Negeri 1 Selong students through the Teams Games Tournament (TGT) type of cooperative learning model (b) Improve the mathematics learning achievement of SMA Negeri 1 Selong students through the Teams Games type cooperative learning model Tournament (TGT) (c) Describe students' responses to the implementation of the cooperative learning model with the Teams Games Tournament (TGT) type. In this study, there were (action research) of 3 cycles. Each cycle consists of several stages, namely: the planning stage, the action stage, and the observation and reflection stages. The subjects of this study were students of class XI IPS 1 semester I of the 2018/2019 academic year, the data obtained were in the form of formative test results and observation sheets of learning activities. Based on the research data, it was found that the average value of students' learning outcomes in the initial conditions in each cycle had increased. In cycle I the average value is 65.40, cycle II the average value is 68.00 and in cycle III the average value is 69.00. The conclusion obtained is that there is a significant increase in learning outcomes through the implementation of the cooperative learning model with the Teams Games Tournament (TGT) type.